2020
DOI: 10.1002/ags3.12379
|View full text |Cite
|
Sign up to set email alerts
|

Essential updates 2018/2019: Current topics in the surgical treatment of pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is highly malignant. While cancers in other organs have shown clear improvements in 5‐year survival, the 5‐year survival rate of pancreatic cancer is approximately 10%. Early relapse and metastasis are not uncommon, making it difficult to achieve an acceptable prognosis even after complete surgical resection of the pancreas. Studies have been performed on various treatments to improve the prognosis of PDAC, and multidisciplinary approaches including non‐surgical treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 209 publications
1
28
0
Order By: Relevance
“…To analyze the effects of PDGL-GEM@CAP/CQ on PDAC metastasis, we grew orthotopic Pan 02 tumors in mice. Such tumors metastasize primarily to the septum and mesentery, which reasonably mimics the clinical situation, in which more than 80% of cases of locally advanced pancreatic cancer metastasize to the peritoneal/omentum and liver 30 , 31 . Similar to the results in the xenograft model, PDGL-GEM@CAP/CQ showed the strongest anti-tumor effects (Figure 7 A-B) and it induced the greatest extent of necrosis as well as the greatest inhibition of fibroblast activation (Figure 7 C).…”
Section: Resultsmentioning
confidence: 81%
“…To analyze the effects of PDGL-GEM@CAP/CQ on PDAC metastasis, we grew orthotopic Pan 02 tumors in mice. Such tumors metastasize primarily to the septum and mesentery, which reasonably mimics the clinical situation, in which more than 80% of cases of locally advanced pancreatic cancer metastasize to the peritoneal/omentum and liver 30 , 31 . Similar to the results in the xenograft model, PDGL-GEM@CAP/CQ showed the strongest anti-tumor effects (Figure 7 A-B) and it induced the greatest extent of necrosis as well as the greatest inhibition of fibroblast activation (Figure 7 C).…”
Section: Resultsmentioning
confidence: 81%
“…38 Since then, many investigators have reported that the antigen was expressed not only in colorectal cancer but also in other gastrointestinal cancers such as PDAC and cholangiocarcinoma. 39,40 In PDAC, serum CA19-9 levels have been reported to reflect the prognosis of PDAC, 11,41,42 and the link between cutoff values of preoperative serum CA19-9 levels and early postoperative recurrence and poor prognosis was also investigated. 20,30,[43][44][45][46][47] On the other hand, SPan-1 is a cancer-related antigen recognized by a monoclonal antibody prepared using the human PDAC cell line SW1990 as an immune antigen, and it is a high-molecularweight mucin-like protein.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the question of how to control such a malignant behavior has become a big challenge, even for patients with resectable PDAC. 11 Previous studies investigated factors related to the uncontrollable behavior of PDAC. 12,13 In particular, serum CA19-9 level is known to correlate with postoperative prognosis, and its association with early postoperative recurrence has also attracted attention.…”
mentioning
confidence: 99%
“…Ductal adenocarcinoma is the most common malignancy of the pancreas. Accordingly, this tumor presents a substantial health problem worldwide 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, this tumor presents a substantial health problem worldwide. 5,6 Through exome sequencing of PDAC surgical specimens, in a very interesting study, Biankin et al demonstrated that the axon guidance gene family was the most frequently altered gene family. 7 Their findings suggest the potential involvement of the nervous system in PDAC carcinogenesis.In clinical pancreatic cancer management, perineural invasion (PNI) is the most significant nerve-related problem.…”
mentioning
confidence: 99%